A novel in-vitro method for assessing contact lens surface dewetting: Non-invasive keratograph dry-up time (NIK-DUT). Issue 6 (December 2017) - Marx, Sebastian; Sickenberger, Wolfgang
Highlights: Non-invasive keratograph dry-up time (NIK-DUT) was developed to assess contact lens dewetting. Combinations of five commercial contact lenses and two lens care solutions were tested. NIK-DUT quantifies the dewetting of a large lens surface area. Dewetting was not uniform across the contact lens surface. Lens care solutions containing surface-active wetting agents delayed dewetting. Abstract: Purpose: This study was designed to develop a novel technique called non-invasive keratograph dry-up time (NIK-DUT), which used an adapted corneal topographer, to analyse in-vitro contact lens surface dewetting and the effects of combinations of lenses and lens care solutions on dewetting. Methods: Variables were assessed to optimise sensitivity and reproducibility. To validate the method, in-vitro dewetting of silicone hydrogel contact lenses (balafilcon A, comfilcon A, lotrafilcon A, lotrafilcon B and senofilcon A) was tested. All lens types were soaked in OPTI-FREE ® PureMoist ® Multipurpose Disinfecting Solution (OFPM) and Sensitive Eyes ® Saline Solution. The mean NIK-DUT, defined as drying of 25% of the placido ring measurement segments (NIK-DUT_S25), was calculated for each lens/lens solution combination and a visual map constructed representing the time and location of the dry-up event. Results: Optimal conditions for NIK-DUT measurement included mounting onto a glass stage with a surface geometry of r = 8.5 mm, e = 0, and measuring with high intensity red or white illumination. This method detected significant differences in contact lens dewetting with different lens soaking solutions. NIK-DUT_S25 for all lenses was longer when pre-soaked in OFPM versus saline. Visual analysis showed that dewetting of contact lenses was not uniform across surfaces and differed between test solutions. Conclusions: NIK-DUT is suitable for detecting differences in dewetting among various contact lenses and lens-care combinations. NIK-DUT can quantify the dewetting of large areas of lens surfaces with little subjective influence. Lens care solutions containing surface-active wetting agents were found to delay surface dewetting of silicone hydrogel lenses.